2022
DOI: 10.1080/00223891.2022.2081809
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of Two Brief Measures of Left-Wing Authoritarianism: A Machine Learning Approach

Abstract: Although authoritarianism has predominantly been studied among political conservatives, authoritarian individuals exist on both "poles" of the political spectrum. A 39-item multidimensional measure of left-wing authoritarianism, the Left-wing Authoritarianism Index, was recently developed to extend the study of authoritarianism to members of the far-left. The present study coupled a fully automated machine learning approach (i.e., a genetic algorithm) with multidimensional item response theory in a large, demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…One reason for this imbalance may be the fact that a sound psychometric self-report measure for LWA in German is missing. Hence, the present research aimed at providing such a measure for German-speaking individuals by adapting the LWAI from English (Costello et al, 2022;Costello & Patrick, 2023) and Spanish (Avendaño et al, 2022). For this purpose, the LWAI was translated from English and Spanish into German.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One reason for this imbalance may be the fact that a sound psychometric self-report measure for LWA in German is missing. Hence, the present research aimed at providing such a measure for German-speaking individuals by adapting the LWAI from English (Costello et al, 2022;Costello & Patrick, 2023) and Spanish (Avendaño et al, 2022). For this purpose, the LWAI was translated from English and Spanish into German.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inverse LWAI-G items may potentially have created an independent method factor which obscured the dimensionality of the latent LWA subscales and expressed itself in the poorer model fits of the longer LWAI-G versions. Yet, despite the inclusion of the inverse items, previous studies found all three versions of the LWAI (i.e., the 39-, the 25-, and the 13-item version) to demonstrate excellent fit indices for the ESEM models in Englishspeaking samples (Costello et al, 2022;Costello & Patrick, 2023) as well as in Spanishspeaking individuals (Avendaño et al, 2022).…”
Section: German Left-wing Authoritarianism Indexmentioning
confidence: 91%
See 2 more Smart Citations
“…Another limitation in the current study concerns our use of a bespoke measure of political orientation. To more fully interpret our work in relation to the broader literature, future studies should consider using previously measures such as the recently developed progressive values scale (Proulx et al, 2023), as well as more established measures of intergroup orientation such as the social dominance orientation scale (Pratto et al, 1994), right-wing authoritarianism scale (Altemeyer, 1983), and the more recent left-wing authoritarianism index (Altemeyer, 1996;Costello & Patrick, 2023).…”
Section: Limitationsmentioning
confidence: 99%